KAJIAN CEMPAKA KUNING (Michelia champaca L.) SEBAGAI TUMBUHAN OBAT - Zumaidar Zumaidar (Jurnal Floratek, 2009)
Study of Yellow Champaca (Michelia champaca L.) as A Medicinal Plant  Zumaidar Fakultas Matematika dan Ilmu Pengetahuan Alam Unsyiah, Banda Aceh ABSTRACT The aim of the research was to appraise uses of yellow champaca (Michelia champaca L.) as a medicinal plant. This research applied participatory rural appraisal method. The data were sampled from 9 sub districts in Banda Aceh by purposive sampling respondents, i.e. tuha peut (ranking people in community), tabib (traditional healer), bidan gampong (traditional midwife) and the community planting yellow champaca.  The result showed that yellow champaca was used as medicine for 21 diseases. Plant organs most used were flowers and leaves. Most of them were mixed with other plant organs.